Experimental study of steam and carbon dioxide microwave plasma for advanced thermal treatment application. (15th September 2020) - Vecten, S.; Wilkinson, M.; Martin, A.; Dexter, A.; Bimbo, N.; Dawson, R.; Herbert, B.
Abstract: Pollution reduction from waste management and energy generation is necessary to mitigate climate change and is one of the major challenges of the 21st century. This can be achieved through the development of innovative energy recovery technologies from biomass and wastes, such as microwave plasma gasification. An envelope of stable CO2 plasma operation is described, by varying working gas flow rate at applied microwave powers between 1 and 6 kW, whereas H2 O plasma operation is possible with flow rate ranging from 20 to 50 g/min and microwave powers between 2.5 and 6 kW. The temperature generated in a large chamber connected to the plasma torch is recorded, reaching up to 850 °C, showing a heterogeneous temperature distribution. In addition, optical emission spectroscopy measurements provide an insight into plasma chemistry and demonstrate the dissociation of CO2 and H2 O molecules at extremely high temperatures of up to 6300 °C assuming local thermodynamic equilibrium. The experimental results demonstrate that the microwave plasma torch provides an ideal environment for gasification with high temperature and very chemically reactive species. This study provides valuable information for the design of microwave plasma gasification reactors with great potential for effective solid feedstock conversion into high quality syngas for energy production. Highlights: CO2 and H2 O plasma operation in a wide range of operating conditions. Temperatures up to 850 °C achieved in chamber connected to the plasma torch. CO2 and H2 O found to dissociate along 14 cm of the plasma plume. Temperatures from 6300 °C to 2300 °C achieved along 14 cm of the plasma plume.